¿Impactó la crisis económica del 2001 la legitimidad democrática en Argentina? - Pedro Aravena Lavín (Revista Enfoques, 2012)
Did economic crisis of 2001 impact the legitimacy of democracy in Argentina? This article discusses the support and satisfaction with democracy in the economic, institutional and political context during some of the worst economic crises suffered by a democratic country. It makes use of the Latinobarometro data, for the years 1997 and 2001. The principal statistical methodology used is an ordered logit estimation, in order to answer the question whether the economic crisis in Argentina affected the legitimacy or support for its democracy. The analysis reveals two main findings. One, it demonstrates the importance of the perception of economic stability. Two, it shows the relevance of corruption and the low level of trust on the institutions concerning the poor assessment of the effectiveness of democracy.